The answer would be 5 like they said
Answer:
80.50
Step-by-step explanation:
profit=$10.50
i would like a brailiest if you dont mind
Answer:
<u>Given function:</u>
- f(x) = (-x + 2)(x + 1)(x +2)
<u>We can rewrite it as:</u>
- f(x) = - (x - 2)(x + 1)(x +2)
<u>Zeros are:</u>
- - (x - 2)(x + 1)(x +2) = 0
- x - 2 = 0 ⇒ x = 2
- x + 1 = 0 ⇒ x = -1
- x + 2 = 0 ⇒ x = -2
As leading coefficient is negative the function is decreasing.
As the function is of degree 3, it is odd.
<u>Considering the above two factors we can define the shape of the graph:</u>
- It is decreasing function with one local minimum and one local maximum.
<em>See the graph and zero's reflected.</em>
Answer:
48
Step-by-step explanation:
Since there is an absolute value, the answer must be positive. Multiply 2 by 8 since two negatives equal a positive. So, |15-47 + 9 - 8 -17|. Then add and subtract to get the answer. -32 + 9 - 8 -17 = -48. |-48| = 48